The Pressure Control of High-Pressure Tubing Based on Difference Equation. (15th May 2020) - Zhang, Yang; Li, Rongjun; Zou, Linhai
Abstract : The situation where fuel enters and exits the high-pressure tubing is one of the important factors that affect the working efficiency of the engine. Based on the simplified high-pressure tubing model, this paper studies the control problems of high-pressure tubing injection and fuel supply under certain circumstances. According to the idea of the difference equation, the paper obtains the opening time of the one-way valve when the pressure value of the high-pressure tubing is kept constant or rises to a specific value by enumerating the opening time of the one-way valve. By establishing the physical model of the high-pressure tubing and the fuel injection nozzle, and then using the enumeration method, the angular velocity of the high-pressure oil pump cam when the pressure of the high-pressure fuel pipe is kept constant can be obtained. Under the more complicated injector model, the control method of the injector is solved by the double enumeration method. The results show that the above model can quickly calculate the optimal working time of the high-pressure fuel pump and needle valve when the accuracy meets the requirements.